The wound healing effect of Iris forentina on full thickness excisional skin wounds: A histomorphometrical study - Mirmalek, Seyed Abbas; Parsa, Tina; Parsa, Yekta; Yadollah-Damavandi, Soheila; Salimi-Tabatabaee, Seyed Alireza; Jangholi, Ehsan; Hosseini, Sahar; Ashkani-Esfahani, Soheil; Abooghadareh, Hanieh; Haghighifard, Erfan (Bangladesh Journal of Pharmacology, 2015)
Iris florentina is an ancient herbal remedy which was prescribed by many physicians due to its positive effects on dermatological problems, specifically skin wounds. Hence, we aimed to investigate the effects of this agent on full-thickness excisional skin wounds in laboratory rats. Three groups of rats (180 ± 20 g; n=8) with 1 cm diameter full-thickness excisional skin wound received daily treatment with I. florentina 10% ointment, and a group with no treatment. By using histomorphometrical methods, the amount of fibroblast population, collagen bundle synthesis, and vascularization (length density, mean diameter and volume density of the vessels) were estimated. Outcome of the study exhibited that the increase in fibroblast proliferation rate, collagen bundle synthesis, vascular density and vascular mean diameter in I. florentina-treated group were significant in comparison to the untreated group (p<0.05). Results indicated that I. florentina can be prescribed as a herbal medicine for treatment of skin wounds or be used as an additional agent for today's common medicines.